2011
DOI: 10.3899/jrheum.101039
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus and Risk of Restless Legs Syndrome

Abstract: These novel data indicate that RLS is more prevalent in women with SLE than in controls. Although obesity was a significant risk factor for RLS in our sample, the predictive covariates examined were limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…In a study by Hassan et al, RLS was found to be more prevalent in women with systemic lupus erythematosus; obesity was also found to be a significant risk factor for RLS. (4) Another study showed that RLS had common comorbidities with rheumatoid arthritis. (17) All of these diseases associated with RLS have immunological and inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Hassan et al, RLS was found to be more prevalent in women with systemic lupus erythematosus; obesity was also found to be a significant risk factor for RLS. (4) Another study showed that RLS had common comorbidities with rheumatoid arthritis. (17) All of these diseases associated with RLS have immunological and inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary RLS occurs due to disease or conditions such as iron deficiency, chronic renal failure or pregnancy. (3) Previous studies have also associated it with systemic inflammatory diseases (4)(5)(6)(7) and small intestinal bacterial overgrowth. (8) Hence, RLS may be related to inflammatory status.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other researchers have found in RA similar prevalence rates for RLS being 27.7–31% [23, 25]. Of interest, elevated prevalence rates for RLS in other connective tissue diseases such as Sjogren's syndrome, scleroderma, and lupus appear [26]. Thus, compared to the general population, there are significantly higher prevalence rates of RLS in patients with rheumatic diseases, especially rheumatoid arthritis.…”
Section: Rls and Rheumatoid Arthritismentioning
confidence: 99%
“…Obesity, neuropsychiatric and kidney involvement and the use of medications such as antihistamines and glucocorticoids may act as confounders when restless legs syndrome (53) and sleep apnea (54) are present.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%